EFFECT OF TRAINING INFORMATION TECHNOLOGY AND COMMUNICATION DRIVING SCHOOL Case of the teaching of O'Brien shot put style - Aymen, Hawani; Maher, Mrayeh; Mohamed, Sami Bousid (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
The purpose of this study was to compare three different pedagogical approaches to training of complex motor skill: shot put style translation (O'Brien). The first is to introduce learning situations using an 'Audiovisual Projection' '(APA). The second is essentially based on demonstration of gesture, supported by verbal instructions (ADG). The third is based exclusively on verbal instructions (ACV). To do this, a group of 87 trainees from three classes of 7th base year participated in this study. Their average age was between 12 and 14 years, an average height of about ± 1.60m and a weight of 55 kg ±. All they had no practical experience in athletic activity, specifically in Shot Put. To each of three classes one of the three approaches was applied as well as 8 sessions alternating with three assessment sessions. The results showed that performance of trainees after using of the first approach (APA) was relatively better than that was achieved with using of other two approaches, especially when training of complex motor tasks, specific to the chosen style of throwing. This allows to deduce the existence of a relationship between complexity of the motor action to be reproduce and interpretation of audiovisual messages, presented by the coach in the middle of training cycle.